Membangun Kepercayaan dan Loyalitas Melalui Pendampingan dan Sosialiasasi Produk pada Nasabah BMT NU Kabupaten Kediri - Anash, Choirul (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
In line with the increasingly high level of competition between financial institutions, every company must strive to be more advanced in developing its competitive capabilities. One of the difficulties faced by BMT NU who are in Kediri is building customer trust, it could be said that not all individuals have trust and responsibility that can make customers loyal and loyal, given that the BMT NU Kediri branch has just opened and was inaugurated and has running almost a year. The results show that trust is the glue that strengthens customer trust and vice versa. If trust has emerged, then the step is to make cooperation easier so that it will benefit both parties. Customer trust has an impact on creating customer loyalty. Customers will be loyal or loyal to a product or service if the customer already has high trust in the product or service.